`3x - 2y = -27, x + 3y = 13` Use matricies to solve the system of equations. Use Gaussian elimination with back-substitution.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

rsWe began by stating our equations as follows: 

3x - 2y = -27

x  + 3y = 13

(NB: Note that I wrote the values of the x variable below each other, values with the y variable below each other and the constants below each other. Also note that the sign before each number is also part of the variable.)

Now we will put the equations in matrix form:

 

`[[3,-2 : -27],[1,3 : 13]]`

Now swap Row 1 with Row 2: We want the numbers in the main diagonal to have the number '1':

`[[1,3 : 13],[3 ,-2 : -27]]`

In Gaussian elimination we want all values below the main diagonal to equal zero. Hence, we shall subtract 3 to Row 3:

`[[1, 3 : 13],[0 ,-5 : -30]]`

Now we want the main diagonal to contain the number '1', hence we divide row 2 by -5: 

`[[1,3 : 13],[0, 1: 6]]`

Now that we have the number 1 across the main diagonal and zero's below the main diagonal we can perform back substitution by substituting the value of y=6 into the first equation:

`x + 3y = 13`

`y = 6`

Therefore `x = -5`

Lets double check our answers

`3*-5 + -2*6 = -15 - 12 = -27`

`-5 + 3 *6 = -5 + 18 = 13`

 

``

 

` `

` `

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial